Przebaczenie jako kategoria współczesnego dyskursu pamięci na przykładzie Kinderszenen Jarosława Marka Rymkiewicza i Słonecznika Szymona Wiesenthala - Napiórkowski, Marcin; Dobrosielski, Paweł (Zagłada Żydów. Studia i Materiały, 2011)
Przebaczenie jako kategoria współczesnego dyskursu pamięci na przykładzie Kinderszenen Jarosława Marka Rymkiewicza i Słonecznika Szymona Wiesenthala Forgiveness as a Category of Modern Memory Discourse as Seen in Jarosław Marek Rymkiewicz’s Kinderszenen and Simon Wiesenthal’s The Sunflower:On the Possibilities and Limits of Forgiveness The text attempts to describe forgiveness as one of the key categories of modern memory discourse. To this end the authors analyzed two texts: Kinderszenen by Jarosław Marek Rymkiewicz and Simon Wiesenthal’s The Sunflower: On the Possibilities and Limits of Forgiveness. Even though the two texts talk explicitly about forgiveness, the unexpressed discourse rules they are based on turn out to be equally interesting. Among them, following Jacques Derrida’s suggestion, it is possible to attribute the biggest importance to the definition of the “unforgivable,” towards which the question about the act of forgiveness occurs to be secondary. Paralleled reading of the two texts allows us then to see that it is not an act of forgiveness or lack of forgiveness, but a call for forgiveness (or for no forgiveness) which constitutes the basic practice of memory today. The attitude toward this call is the basis on which memory communities constitute themselves.